ANALISIS KETERCAPAIAN INDIKATOR BUDI PEKERTI LUHUR SISWA DALAM PEMBELAJARAN IPA SMP PADA MASA PPKM PANDEMI COVID-19 - Abdul Farih Nadhif; Ahmad Qosyim (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to analyze the achievement of students’ noble character aspect in science learning during the Covid-19 pandemic. This study was descriptive research with a quantitative approach. The research subjects were nineteen female students of VII-B class and one science teacher of Jati Agung Junior High School with the sampling technique used was purposive sampling. The data collection techniques used were interviews and questionnaires. The data analysis techniques used in this study were data reduction processes, information presentations, and conclusions. The results of this study showed that all students have a particularly good religious character, and most students also have honest, responsible, confident, and tolerant characters. So, it can be concluded that five aspects of noble character that are analyzed by the researcher in science learning are following the noble character aspect. The study result proved this accordance where student’s noble character aspect in a very good category.